Narrative Review of Biomarkers in Patients with Peri-implantitis - Ghodratizadeh, Soroush; Shenasa, Naghmeh; Tavakol, Omid; Mohamadinia, Mehdi; Gandomkar, Hossein; Behnam Roudsari, Mohammadreza; Sadighi, Khayrolnesa (Galen Medical Journal, 2024)
Background: Peri-implantitis is caused by the breakdown of homeostasis between the host’s response to microbial pathogens. The aim of this study was to assess clinical studies by use of a systematic review on some mouth biomarkers except of interleukin, active metalloproteinase (MMP) and TNF-α in peri-implantitis patients. Materials and Methods: A regular and complete search was conducted through mesh keywords by search of the Science Direct, PubMed, Google Scholar database until August 6, 2024. Those articles that reported biomarkers other than interleukin, active metalloproteinase (MMP) and TNF-α were included in this review. The outcome was defined to be peri-implantitis. Two reviewers have searched and screened the articles completely independently of each other. For assessing the quality of the studies, risk of bias tool developed by Downes et al. were used. Results: In general, 41 articles were found for this review. Based on our findings, key markers include Neutrophil extracellular traps (NETs), proinflammatory cytokines, oxidative stress markers, salivary biomarkers, microRNAs, extracellular vesicles, proteomic and metabolomic changes, and microbial markers. Stress markers like cortisol also play a role. Risk of bias is low in most studies. Conclusion: Biomarkers found in this study suggest a complex cascade of events involved in pathophysiological pathway of peri-implantitis including the microbial colonization, immune activation, bone resorption, oxidative stress, vascular changes, stress responses, and epigenetic modifications